Recent Advances in Transition-Metal-Catalyzed Selective C–H Alkoxycarbonyldifluoromethylation Reactions of Aromatic Substrates - Ju, Guodong; Tu, Guanglian; Zhao, Yingsheng (Synthesis, 2021)
Fluorine is well-known as a very special element. Approximately 30% of agrochemicals and 20% of all drugs contain fluorine; most of those compounds have unique functions in biochemistry, pharmacy, and bioscience and those containing alkoxycarbonyldifluoromethyl functional groups often have irreplaceable roles. Therefore, the selective introduction of alkoxycarbonyldifluoromethylated functional groups into various aromatic substrates has significant practical application. This review describes recent advances in selective alkoxycarbonyldifluoromethylation of aromatic substrates by using different catalytic strategies (cyclometalated ruthenium complex, transient regulating and visible-light-induced strategies).1 Introduction2 para-C–H Alkoxycarbonyldifluoromethylation of Aromatic Derivatives2.1 Ruthenium Catalysis2.2 Palladium Catalysis2.3 Visible-Light Catalysis2.4 Iron Catalysis3 meta-C–H Alkoxycarbonyldifluoromethylation of Aromatic Derivatives3.1 Ruthenium Catalysis3.2 Palladium Catalysis4 The Influence of Transition Metals and Directing Groups on Site Selectivity of Alkoxycarbonyldifluoromethylation4.1 The Influence of Directing Groups on the Site Selectivity of Alkoxycarbonyldifluoromethylation4.2 The Influence of Transition Metals on the Site Selectivity of Alkoxycarbonyldifluoromethylation5 Conclusions
Keywords: C–H activation; alkoxycarbonyldifluoromethylation; transition metal-catalyzed; site selectivity; radical